Stimulation of oxidative burst in human monocytes by lipoteichoic acids. - Levy, R (1990)
Lipoteichoic acid isolated from Streptococcus faecalis or Streptococcus pyogenes caused direct activation of the respiratory burst in human peripheral blood monocytes. This activity appears to be related to the ability of lipoteichoic acid to bind to the monocyte membrane and trigger the polarization of receptors (capping).